Biomimetic Design of Turbine Blades for Ocean Current Power Generation - Enrique Eduardo Hernández Montoya; Edgar Mendoza; Eize J. Stamhuis (Biomimetics, 2023)
The enhancement of energy technology and innovation play a crucial role in order to meet the challenges related to global warming in the coming decades. Inspired by bird wings, the performance of a bio-inspired blade assembled to a marine turbine model, is examined. Following a biomimetic pathway, the aerodynamic performance of the bird wings of the species Common Guillemot (Uria aalge) was tested in a wind tunnel laboratory. Based on our results, we derived a bio-inspired blade model by following a laser scanning method. Lastly, the bio-inspired blades were assembled to a marine turbine model and tested in a large flow tank facility. We found efficiencies (Cp) up to 0.3 which is around 53% of the maximum power that can be expected from the turbine model according to the Betz approach. Our findings are analyzed in the discussion section as well as considerations for future research.